2020
DOI: 10.1016/j.leaqua.2019.101338
|View full text |Cite
|
Sign up to set email alerts
|

Natural experiments in leadership research: An introduction, review, and guidelines

Abstract: Endogeneity is a serious challenge for leadership research. To overcome the problem, researchers increasingly rely upon experimental designs, such as laboratory and field experiments. In this paper, we argue that natural experiments-in the form of standard natural experiments, instrumental variable, and regression discontinuity designs-o↵er additional opportunities to infer causal relationships. We conduct a systematic, cross-disciplinary review of 87 studies that leverage natural experimental designs to inqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 130 publications
(125 reference statements)
1
56
0
Order By: Relevance
“…Various approaches can be used, including field experiments, regression discontinuity designs, and natural experiments. Such econometric designs are new for many work and organizational psychologists, but accessible overviews are available (Antonakis et al, 2010 ; Sieweke and Santoni, 2020 ). We urge scholars to check these out.…”
Section: Discussionmentioning
confidence: 99%
“…Various approaches can be used, including field experiments, regression discontinuity designs, and natural experiments. Such econometric designs are new for many work and organizational psychologists, but accessible overviews are available (Antonakis et al, 2010 ; Sieweke and Santoni, 2020 ). We urge scholars to check these out.…”
Section: Discussionmentioning
confidence: 99%
“…However, candidate effects can be particularly hard to discern in Westminster‐type parliamentary systems, where national and partisan factors can exert a powerful sway on voter choices (Gaines, 1998). Moreover, despite strong ecological validity in field studies (Sieweke & Santoni, 2020), our research context (i.e., candidates campaigning in a national election) placed constraints on what information could be collected and when.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies, whether cross-sectional snapshots or longitudinal, are riddled with endogeneity bias (i.e., confounded because of omitted causes); alarmingly, in multiple surveys of the literature, we have found that most reported results are false (Antonakis et al, 2019; Antonakis et al, 2010; Fischer et al, 2017). Researchers using field data need to up their game and use designs that are robust and allow for causal claims to be made (Sieweke & Santoni, 2020).…”
Section: Research In the Covid And Post-covid Eramentioning
confidence: 99%